(untitled) (Research, Society and Development, 2019)
It is notorious the difficulty that some doctors have difficulties when they are dealing with the public. Faced with this problem, objective of this study was to present a teaching methodology that allows for the training of teachers in the period of internship in the Family Health Strategy in a course of medicine. A qualitative study was carried out, since the main quest was the improvement of the quality of affairs in the Family Health Strategy. It was held a workshop based on Problematization Methodology and applied an initial survey and a questionnaire after application of the workshop the initial survey showed that the Preceptors little knew the tools of family approach and after the workshop of family approach so necessary to this type of strategy, it became apparent that great art of affairs presented greater resourcefulness in the majority of the resolution of the problems of circulation Clinic. It is concluded that the workshop was an important teaching tool enabling empower the Preceptors in tools of family approach to transmit to students such knowledge of critical-reflexive manner.